Modeling of electromagnetic energy harvesting from vehicle damper in shock absorber of motorcycle. Issue 5 (March 2020) - Susilo, S; Abdullah, S; Satria, D; Ghifari, M R; Hermawan, B A
Abstract: Modeling of electromagnetic energy harvesting on the vehicle suspension system is presented in this paper. This study uses the up and down movement oscillation of the shock absorber to vibrate the SDOF module which is consist coil and a permanent magnet. The mathematical model is developed by using Faraday law to estimate the electrical response of the energy harvester. The effect of resistance load is admitted in the mathematical model its effect on the performance of the energy harvester. The effect is investigated for different values of frequency and resistance load. This method proposed regenerative absorber is effective and practical for renewable energy applications.